Potential and Efforts to Increase Competitiveness Creative Industries in Banda Aceh - Ayuni, Devi; Utomo, Mohammad Noor; Safitri, Julia; Pujiwati , I (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
Banda Aceh, which was recognized as a "Creative City" at the end of 2017, marks a significant milestone in the development of Aceh's creative economy. The city has become a hub for creative industries with culinary, craft, fashion, and performing arts subsectors as key drivers. This study uses the Diamond Porter and Kotler models, as well as quantitative methods with a multi-criteria approach, to identify the potential of the creative industry in Banda Aceh and formulate strategic steps to increase its competitiveness. The main findings conclude that there are three main criteria for strategy, namely opportunity, government role, and demand conditions, with important subcriteria such as technological tools, policies, and product variety. An optimistic strategy is set as a top priority to increase the competitiveness of the creative industry in the craft subsector in Banda Aceh. These findings provide practical guidance for industry players and local governments, support the development of sustainable creative industries in the region, and potentially contribute to further research in similar contexts